Comparing the economic development of the Ukraine and Kazakhstan (Journal of Economic Research & Business Administration, 2015)
In this paper the authors analyze the economy of Ukraine and Kazakhstan in terms of macroeconomic analysis to identify similarities and differences of their development in the context of the fact that these countries have chosen different strategies regarding the integration processes. Kazakhstan and Ukraine are the second and third largest economies respectively in CIS, they have no common borders, but have some common characteristics. Both states are important trading partners of Russia and have a few similarities of foreign policy and economic environments.
Keywords: economic development; macroeconomic indicators; Ukraine; Kazakhstan